(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Budhathoki N, Dhakal S, Dyola U. 2021. Diversity of hoverflies (Diptera: Syrphidae) in Nagarjun, Shivapuri Nagarjun National Park, Nepal. Biodiversitas 22: 5382-5388. Hoverflies are recognized as potential pollinators of a wide range of wild plants. This study explored the abundance and diversity of hoverflies over three different seasons from October 2018 to April 2019 in two different study sites, i.e. forest and grassland at Nagarjun of Shivapuri Nagarjun National Park, Nepal. Each site of the study area was further divided into five sampling transect stations. Hoverflies were collected from each station by using two methods as pan trap sampling and transect sweeping sampling. Overall, a total of 373 specimens representing 13 species under nine genera of two subfamilies (Syrphinae and Eristalinae) were recorded. The abundance and diversity of hoverflies varied seasonally, the maximum number of individuals and diversity were recorded from the spring season, whereas the minimum number of individuals and diversity were found in the winter season. In addition, forest habitat consists of the highest abundance and diversity of hoverflies, whereas grassland consists of the lowest abundance and diversity. The analysis done by using generalized linear modeling (GLM) revealed climatic parameters such as temperature and humidity had a varying effect on the abundance of hoverflies. However, both these parameters had not any significant influence on the number of hoverfly species.